Characteristics of COVID-19 Patients Based on the Results of Nucleic Acid and Specific Antibodies and the Clinical Relevance of Antibody Levels - Chen, Hao (Front Mol Biosci, 2021)
Combination of nucleic acid and specific antibody testing is often required in the diagnosis of COVID-19, but whether patients with different nucleic acid and antibody results have different laboratory parameters, severities and clinical outcomes, has not yet been comprehensively investigated. Thus, according to different groups of nucleic acid and antibody results, we aimed to investigate the differences in demographic characteristics, and laboratory parameters among the different groups and predict their clinical outcomes. In our study, nasopharyngeal swab nucleic acids and antibodies were detected by reverse-transcription polymerase chain reaction and chemiluminescence, respectively. Patients with confirmed COVID-19 with different severities, were divided into the PCR(+)Ab(+), PCR(+)Ab(−), and PCR(−)Ab(+) groups. Demographic characteristics, symptoms, comorbidities, laboratory parameters, and clinical outcomes were compared among the three groups. The correlation of antibodies with laboratory parameters and clinical outcomes was also explored, and antibodies were used to predict the timing of nucleic acid conversion. We found that a total of 364 COVID-19 patients were included in the final analysis. Of these, a total of 184, 37, and 143 patients were assigned to the PCR(+)Ab(+), PCR(+)Ab(−), and PCR(−)Ab(+) groups, respectively. Compared to patients in the PCR(+)Ab(−) or PCR(−) Ab(+) groups, patients in the PCR(+)Ab(+) group presented worse symptoms, more comorbidities, more laboratory abnormalities, and worse clinical outcomes (P < 0.05). In addition, the levels of IgG, IgM, and IgA were all significantly correlated with the days of hospitalization, days of PCR turning negative, and multiple laboratory parameters (P < 0.05). Meanwhile, combined IgM, IgA, and IgG predicted the days of PCR turning negative within 1 week. The best performance was achieved when the cut-off values of IgM, IgG, and IgA were 3.2, 1.8 and 0.5, respectively, with a sensitivity of 73% and specificity of 82%. In conclusion, COVID-19 patients who were both positive for nucleic acids and antibodies presented with worse clinical features, laboratory abnormalities, and clinical outcomes. The three specific antibodies were positively correlated with clinical outcomes and most laboratory parameters. Furthermore, antibody levels can predict the time of nucleic acid conversion.